2015
DOI: 10.31768/2312-8852.2015.37(1):70-72
|View full text |Cite
|
Sign up to set email alerts
|

Functional Activity of Cd34-Positive Cells in Chronic Myeloid Leukemia Patients With Different Response to Imatinib Therapy

Abstract: Introduction: It is believed that the reason of the leukemic clone cell resistance to treatment with tyrosine kinase inhibitors during chronic myeloid leukemia (CML) is mutations in the genome of an early bone marrow progenitor cells that are CD34-positive. Such cells, regardless of treatment, acquire ability to proliferation and differentiation. This leads to the re-expansion of the CD34 + cells. Aim: to determine the CD34 antigen expression in bone marrow and peripheral blood cells in CML patients with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In another study (12), the results of flow cytometry analysis showed that in patients with the acquisition of resistance to imatinib the number of CD34+ cells increases in the bone marrow and peripheral blood.…”
Section: Discussionmentioning
confidence: 94%
“…In another study (12), the results of flow cytometry analysis showed that in patients with the acquisition of resistance to imatinib the number of CD34+ cells increases in the bone marrow and peripheral blood.…”
Section: Discussionmentioning
confidence: 94%
“…CML is a myeloproliferative neoplasm characterized by the expansion of the early hematopoietic progenitor cells pool which express CD34 antigen [ 31 ]. CML cells were differentiated from other hematopoietic cells based on the intensity of green fluorescence signals emitted by the CD34 antibody (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CML is a myeloproliferative neoplasm characterized by the expansion of the early hematopoietic progenitor cells pool which express CD34 antigen [31]. CML cells were differentiated from other hematopoietic cells based on the intensity of green uorescence signals emitted by the CD34 antibody (Fig.…”
Section: Resultsmentioning
confidence: 99%